Tenth Five Year Plan 2002-2007 and Annual Plan 2002-2003 [Volume-II] National Capital Territory of Delhi - Planning Commission (Planning Commission, 2002)
Health of the people is not only a desirable goal but also an essential investment in Human resources. The National Health Policy reiterated India’s Commitment to attain Health For All (HFA) by 2000 AD. Primary health care has been accepted as the main instrument for achieving this goal. Accordingly, a vast network of health care facilities in all areas & locations of this Territory have been established.
Planning Department, Government of National Capital Territory of Delhi